A Collective Retirement Model : Identification and Estimation in the Presence of Externalities - Pierre-Carl Michaud; Frederic Vermeulen (Institute for the Study of Labor (IZA), 2004)
We study the labor supply dynamics of elderly couples by means of a structural collective model. The model allows for general externalities with respect to spouses? leisure. Preferences and the intrahousehold bargaining process are identified by using panel data with couples and individuals who turned into widow(er)hood in the covered period. The model does not only look at the extensive margin (working versus being retired), but also at the intensive margin (how many hours are worked) and the claiming decision for social security benefits. We apply the model to American households coming from the first five waves of the Health and Retirement Study. We also provide model simulations for two widely discussed reform proposals; more specifically the abolition of the earnings test and the elimination of the spouse benefit. The model simulations reveal only small changes in labor supply of elderly couples.
Keywords: D13; J26; J22; H31; 330; collective household models; labor supply; retirement; social security; identification; Ältere Arbeitskräfte; Altersgrenze; Erwerbstätigkeit; Haushaltsökonomik; Vereinigte Staaten